The Influence of Profitability, Leverage, Dividend Policy and Institutional Ownership on Firm Value LQ45 - Hanifa Wanda Kusumawati; Kartika Hendra Titisari; Purnama Siddi (Journal of Indonesian Science Economic Research, 2021)
This study aims to determine the effect of profitability, leverage, dividend policy, liquidity and institusional ownership on the value of the LQ45 company in 2016 - 2019 which is listed on the Indonesia Stock Exchange (IDX). The method used in this research is quantitative method. Sampling was done by purposive sampling, in order to obtain a sample of 19 companies. Hypothesis testing uses multiple linear regression method. The results showed that the variables of profitability, leverage and liquidity had an effect on firm value, but the variables of dividend policy and institusional ownership had no effect on firm value.